ABO blood types and postpartum depression among Chinese women: A prospective cohort study in Tianjin, China. Issue 6 (3rd July 2018) - Song, Chunhua; Leng, Junhong; Wang, Leishen; Li, Wei; Zhang, Shuang; Wang, Wei; Liu, Pingying; Zhang, Jing; Xie, Bin; Li, Weidong; Chan, Juliana C. N.; Yang, Xilin
ABSTRACT: Postpartum depression is associated with adverse consequences for mother and offspring. The heritable ABO blood group has been associated with multiple diseases, including mental illness and diabetes. We explored the association of ABO blood group and postpartum depressive symptoms (PPDS) in a population-based cohort of pregnant Chinese women. From 2010 to August 2012, we recruited 8842 pregnant women with a mean age of 28.5 years ( SD : 2.94) and mean body mass index of 22.4kg/m 2 ( SD : 3.45) in Tianjin, China. We used the Mainland Chinese version of the Edinburgh Postnatal Depression Scale after delivery with a cutoff score of 10 to define PPDS. Odds ratios (ORs) and 95% conﬁdence intervals (CIs) for PPDS were obtained using binary logistic regression. Of 8842 women, 8.5% (n = 747) developed PPDS. Compared to those with blood group B, women with blood groups A, AB or O had a higher odds of PPDS (adjusted ORs: 1.23 (95% CI: 1.13–1.40), 1.31 (95% CI: 0.98–1.74), and 1.30(95% CI:1.03–1.60), respectively). Blood group B was associated with reduced odds of PPDS in pregnant Chinese women. If replicated in other studies, non-blood group B may be a useful risk factors for PPDS in Chinese pregnant women.